VALUE FOCUSED THINKING TO DETERMINE ALTERNATIVE STRATEGIES IN BERKAH JAYA FLORIST BUSINESS - Aprilian, Adho Kurnia Lefitra; Novani, Santi (Journal of Business and Management, 2018)
Abstract. One of the products that Indonesians typically use to reward certain moments is a flowered board. The flower giving of the board itself, is actually has a meaning as a symbol of appreciation of an achievement (Twsflorist, 2016). Berkah Jaya is one of the flower board company located in Bandung that was established in August 2017. According to Berkah Jaya owner, Mochamad Ramdhani (2017), Berkah Jaya implements several strategies in dealing with the tight flower market competition. One way is to modify the display of flower board products. Since its establishment, the demand for Berkah Jaya order has continued to increase. High demand orders are a promising business opportunity. But every month, Berkah Jaya on average is only able to do half of the number of incoming orders, because the conditions experienced Berkah. Therefore Berkah Jaya has not gained maximum profit. Based on the results of the Cost Benefit Analysis that has been done, it can be concluded that there are several possible alternatives to be applied by the company to achieve company objectives. Once we know some possible alternatives to apply, then we create a timeline of alternative implementation.Keywords: Cost-Benefit Analysis, Florist, Flowered Board, SWOT, Value-Focused Thinkin,